A Study on Arundhati Roy’S Novel ‘The God of Small Things’: Exploring the multifaceted themes of Arundhati Roy's iconic novel (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Arundhati Roy’s The God ofSmall Things is a polysemic novel which can be interpreted at severallevels. It may be said that the novel is a satire on politics attackingspecifically the Communist establishment. It may be treated as a family saganarrating the story of four generations of a Christian family. It may also betreated as a novel having religious overtones: One may also call it a protest novelwhich is subversive and taboo-breaking.